Language Interaction in Shor-Russian Bilinguals’ Speech in Southern Siberia - Zoya Ivanovna Rezanova; Anna Vladimirovna Dybo (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2019)
The authors aim at presenting the results of their analysis of deviations from the speech norm (DSN) at the phonetic, morphological-syntactic and lexical levels in the speech of bilinguals in one special case of ethno-linguistic contacting, i.e. Shor-Russian bilingualism. The conclusions are based on the data of field recordings of bilingual speech and result from a newly developed annotation system (error annotation) in the Russian Speech Corpus of Russian-Turkic bilinguals in Southern Siberia. The authors find and characterise intralingual (interaction of the national language forms, written and oral communication modes) and cross-language (influence of the native Turkic languages) sources of influences on the Russian speech of bilinguals. The article substantiates the use of the norms of Russian literary writing as a speech standard, methods of analysis and literature (including theoretical works), the analysis of which makes it possible to conclude about the nature of the influences generating DSN. The regularity of the Shor-Russian interfering phenomena is noted in the speech of speakers of all the three age categories under consideration, while dialectal influences are recorded in the communication of respondents over 65 years of age. The study comprises a sociolinguistic analysis of the linguistic situation, a sociolinguistic and linguistic (focusing on the presentation of bilingual language experience) portrayal of bilinguals whose texts are analysed using standard and adapted questionnaires, consistently applied. The conclusion about a DSN type is made using the data on the norms of the Russian literary language, on variants of their implementation in written and oral spontaneous communication, on the peculiarity of the norms of territorial and social variants of the Russian language in the places of residence of the respondents and using the data on regular structures of the Shor language.